Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
c-a=B
Step-by-step explanation:
if A+B=c then you subtract a from c and you get b
Answer:
C. c - a = b
Step-by-step explanation:
a + b = c
There are many ways to rearrange this equation. This can be done through addition and subtraction.
First, let's handle a. a is positive; therefore, we should subtract it.
a + b = c
b = c - a
Next, let's handle b. b is also positive; therefore, we should subtract it.
a + b = c
a = c - b
Finally, we will handle c. c is once again positive; therefore we should subtract it. However, it is the only variable on the right side, which would leave 0. This is not an option, so we will not look at this.
From our options, we can see that we have produced: b = c - a
This is an option, which has been written as c - a = b.
Therefore, your answer is C. c - a = b
Hope this helps!
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.